1921
DOI: 10.1002/ar.1090210203
|View full text |Cite
|
Sign up to set email alerts
|

The character of the lymphatics in experimental edema

Abstract: El cariicter de 10s linfiiticos en el edema experimental.Los autores han producido edema en el renacuajo mediante:(1) Extirpaci6n del pronefros; (2) extirpacibn del esbozo del coras6n; (3) impidiendo el desarrollo de la musculatura del coraz6n linfAtico, y (4) en conexi6n con la inflamaci6n ashptica. 1. En 10s individuos sin pronefros, el liquido plasmtitico se acumula tan solo en la cavidad abdominal. La circulaci6n sanguinea se hace miis dificil y el desarrollo de 10s vasos sangufneos se retarda. Los linfiit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1930
1930
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We have already shown that such is their condition in the ear of the mouse (5) rendered edematous by paintings of xylol; and more recently Pullinger and Florey (12), using the same organ, have shown that local edema following injection of saline or 1 to 1,000 histamine solution into the tissues leads to dilatation of the lymph channels. Clark and Clark (13) have shown that lymphatics in edematous tadpoles are dilated and filled with fluid, and Drinker and Field (6) report that swelling of the tissues after complete venous blockage does not shut off large collecting lymphatics. Why, then, do the lymphatics function so well in edematous skin of nephritic edema and scarcely at all in that of cardiac patients?…”
Section: Discussionmentioning
confidence: 99%
“…We have already shown that such is their condition in the ear of the mouse (5) rendered edematous by paintings of xylol; and more recently Pullinger and Florey (12), using the same organ, have shown that local edema following injection of saline or 1 to 1,000 histamine solution into the tissues leads to dilatation of the lymph channels. Clark and Clark (13) have shown that lymphatics in edematous tadpoles are dilated and filled with fluid, and Drinker and Field (6) report that swelling of the tissues after complete venous blockage does not shut off large collecting lymphatics. Why, then, do the lymphatics function so well in edematous skin of nephritic edema and scarcely at all in that of cardiac patients?…”
Section: Discussionmentioning
confidence: 99%
“…By means of specific markers for LECs, Wigle and Oliver [16] have detected the anlagen of the lymphatics at embryonic day (ED) 9.5 in mouse embryos. The early studies on the development of lymphatic vessels have employed injection techniques, serial sectioning of embryos [17,18], and observation of living animals [19,20]. These studies could not clarify if LECs are derived from scattered lymphangioblasts in the mesenchyme [21,22] or by sprouting from specific parts of embryonic veins [17], or by both mechanisms [23].…”
Section: Embryonic Developmentmentioning
confidence: 99%